2016
DOI: 10.1016/j.jcv.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among pregnant women in Haiti: A cross-sectional serosurvey

Abstract: Background Hepatitis B vaccine administered shortly after birth is highly effective in preventing mother to child transmission (MTCT) of infection. While hepatitis B vaccine was introduced in Haiti as part of a combined pentavalent vaccine in 2012, a birth dose is not yet included in the immunization schedule. Objectives Determine the seroprevalence of hepatitis B virus (HBV) infection among pregnant women to evaluate the risk of MTCT. Study design We selected 1364 residual serum specimens collected during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…Likewise, Lao et al [34] have reported a positive correlation between age and prevalence (p = 0.006) in Hong Kong. While a significant association was recorded between age and HBsAg seropositivity in the some studies [18,34], in the others [26,29,31,33,[35][36][37] no significant difference have reported between age and HBsAg seropositivity. In the present study, the highest seroprevalance of HBsAg was among the age group 36-45 years.…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, Lao et al [34] have reported a positive correlation between age and prevalence (p = 0.006) in Hong Kong. While a significant association was recorded between age and HBsAg seropositivity in the some studies [18,34], in the others [26,29,31,33,[35][36][37] no significant difference have reported between age and HBsAg seropositivity. In the present study, the highest seroprevalance of HBsAg was among the age group 36-45 years.…”
Section: Discussionmentioning
confidence: 88%
“… Denotes prevalence (total) derived from samples of PLHIV pregnant women among the population group PLHIV (heterosexual and pregnant women) including: Cameroon (2) 9.3%, 14.6%; Cote D’Ivoire (1) 9.0%; Nigeria (1) 4.2%; South Africa (3) 6.2%, 3.4%, 2.1%; Malawi (1) 8.7%; Rwanda (1) 2.4%; Tanzania (1) 6.2%; Uganda (1) 4.9%; Brazil (5) 1.9%, 0.5%, 2.3%, 0.9%, 1.2%; USA (1) 2.9%; Canada (1) 5.6%; Haiti (1) 2.4%; France (2) 6.0%, 6.9%; the Netherlands (1) 4.9%, and Morocco (1). …”
Section: Resultsmentioning
confidence: 99%
“…For example, the Japanese foreign born distribution was reported to be 27% in the US [ 15 ]. Next, we collected race/ethnicity- and nativity-specific HBsAg prevalence data among White [ 11 ], Hispanic [ 11 , 18 ], Black [ 11 , 19 21 ] and APIs [ 2 , 11 , 19 , 22 24 ] in the US from the literature. Jung et al reported a 0% (353 people tested) of HBsAg prevalence among 70+ year old Hispanic population, which we decided not to take and assume the same prevalence for 60+ as the 60–69 age-group (0.38%).…”
Section: Methodsmentioning
confidence: 99%